Clinical and inflammatory biomarkers of inflammatory bowel diseases are linked to plasma trace elements and toxic metals; new insights into an old concept - Amerikanou, Charalampia; Karavoltsos, Sotirios; Gioxari, Aristea; Tagkouli, Dimitra; Sakellari, Aikaterini; Papada, Efstathia; Kalogeropoulos, Nick; Forbes, Alastair; Kaliora, Andriana C. (Frontiers in Nutrition, 2022)
Background: Inflammatory bowel diseases (IBD) are chronic immune-mediated diseases, mainly represented by Crohn’s disease (CD) and ulcerative colitis (UC). Several environmental factors have been proposed to contribute to disease pathogenesis, amongst which are metals. These can affect the immune system and may be associated with IBD. The aim of the present cross-sectional study was to investigate blood levels of metals in IBD patients and to examine possible associations with clinical and inflammatory disease markers. Methods: In total, 76 CD patients, 39 UC patients and 38 healthy controls were included. Blood and stool samples were collected. Metals were quantified in plasma samples using inductively coupled plasma mass spectrometry. Results: There were more abnormalities of circulating metals in CD than in UC when compared to healthy controls. CD: Concentrations of the essential trace elements zinc and selenium were lower in CD patients than the controls. Chromium was negatively associated with serum IL-6 (Beta:-3.558, p=0.011), and caesium with faecal calprotectin (Beta:-0.481, p=0.038) and serum IL-10 (Beta:-1.912, p=0.050). In contrast, copper was positively associated with C-reactive protein (Beta:2.548x102, p=0.033). UC: In UC, a negative association of iron (Fe) with serum myeloperoxidase levels (Beta: -1.270x103, p=0.044) was detected. Thallium, a hazardous metal, however, was positively associated with disease activity (Beta:3.899, p=<0.01). Conclusion: In conclusion, our study offers new insights into the relations of metals with IBD. Further research should focus on the evaluation of the above associations and potential underlying mechanisms.